2021
DOI: 10.1016/j.actbio.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Combining tunable proteolytic sequences and a VEGF-mimetic peptide for the spatiotemporal control of angiogenesis within Elastin-Like Recombinamer scaffolds

Abstract: One of the main challenges in regenerative medicine is the spatiotemporal control of angiogenesis, which is key for the successful repair of many tissues, and determines the proper integration of the implant through the generation of a functional vascular network. To this end, we have designed a three-dimensional (3D) model consisting of a coaxial binary elastin-like recombinamer (ELR) tubular construct. It displays fast and slow proteolytic hydrogels on its inner and outer part, respectively, both sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Upon macroscopic and histological evaluation, we did not observe major changes despite minor inflammation sites in muscles where the biomaterial was injected alone or with MSCs and a small collagen reaction in muscles injected with MSCs. In accordance with these findings, some groups have also described the absence of important inflammation response when ELR-based hydrogels are injected subcutaneously in mice (Ibáñez-Fonseca et al, 2018;Ibáñez-Fonseca et al, 2020;González-Pérez et al, 2021). It has also been reported that there is no effect on collagen fiber distribution neither in a situation of ischemia nor after treatment with biomaterials or MSC (Amani et al, 2021) as is observed in our samples.…”
Section: Discussionsupporting
confidence: 92%
“…Upon macroscopic and histological evaluation, we did not observe major changes despite minor inflammation sites in muscles where the biomaterial was injected alone or with MSCs and a small collagen reaction in muscles injected with MSCs. In accordance with these findings, some groups have also described the absence of important inflammation response when ELR-based hydrogels are injected subcutaneously in mice (Ibáñez-Fonseca et al, 2018;Ibáñez-Fonseca et al, 2020;González-Pérez et al, 2021). It has also been reported that there is no effect on collagen fiber distribution neither in a situation of ischemia nor after treatment with biomaterials or MSC (Amani et al, 2021) as is observed in our samples.…”
Section: Discussionsupporting
confidence: 92%
“…The cells can bind to the scaffolds and then proliferate and differentiate ( Avolio et al, 2017 ; Turnbull et al, 2020 ; Abdollahiyan et al, 2021 ; Bianchi et al, 2021 ; Masson-Meyers and Tayebi, 2021 ). In addition, growth factors can be incorporated into the scaffolds to advance tissue regrowth and repair ( Hormozi et al, 2017 ; Kakudo et al, 2020 ; González-Pérez et al, 2021 ). To meet the clinical needs, the scaffolds for soft tissue repair should have tissue-matching mechanical properties, excellent biocompatibility, and appropriate biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…opening and closing cycles) ( Urry et al, 1976 ). These protein-engineered polymers can prevent the formation of fibrotic tissue and promote the pro-healing type-2 macrophages over the pro-inflammatory type-1 macrophages ( Ibáñez-Fonseca et al, 2020 ; González-Pérez F. et al, 2021 ). Moreover, their recombinant nature makes them a multivalent platform for the development of cell-instructive hydrogels for in situ TE with precise control of their properties and composition ( Girotti et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, multiple bioactive motifs (e.g., cell-adhesive motifs or protease-sensitive sequences among others) can be incorporated into their backbone, thus conferring enhanced cell migration and matrix remodeling capacities. Recent studies have explored the development of ELR hydrogels with protease cleavage sites and bioabsorbable properties, which demonstrated to favor stromal cell-colonization, degradation and remodeling upon the in vivo implantation ( Flora et al, 2019 ; González-Pérez F. et al, 2021 ; Contessotto et al, 2021 ). This cell-mediated degradation capacity is highly interesting for an in situ approach, in which a balance between the scaffold degradation and the cell colonization and remodeling is required.…”
Section: Introductionmentioning
confidence: 99%